Transparansi Pengungkapan Penyisihan Terhadap Manajemen Laba Akrual - Yuni Fatma; Nurzi Sebrina (Universitas Negeri Padang, 2019)
This study aims to examine the effect of transparency in disclosure of allowance for accrual earnings management. This research is classified as causal associative research. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange in 2013-2017. By using the purposive sampling method, there are 30 companies as research samples. Overall accrual earnings management uses discretionary accruals, transparency is measured by the allowance disclosure indicator. The type of data used is secondary data obtained from www.idx.co.id. The analytical method used is panel cross section regression analysis. The results of this study indicate that transparency in disclosure of allowance is not able to explain the variance of accrual earnings management in the observation company so that the research hypothesis is rejected.